2012
DOI: 10.7883/yoken.65.322
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between stx Genotype and Stx2 Expression Level in Shiga Toxin-Producing Escherichia coli O157 Strains

Abstract: SUMMARY:To determine the expression level of Shiga toxin (Stx) 2-related toxins (Stx2 and Stx2c) produced by each of 33 Stx-producing Escherichia coli (STEC) O157 strains, stx2 and stx2c mRNAs (stx2-related mRNA) were measured using real-time PCR with primers that recognize sequences common to stx2 and stx2c. The amount of Stx2 and Stx2c protein was measured using a reversed passive latex agglutination (RPLA) kit. Expression of stx2-related mRNA was significantly higher in STEC O157 strains carrying the stx2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The proportion of individual STEC isolates that carried both stx2c and stx2d concurrently was higher compared to the results of two studies, which previously reported single strains that possess both subtypes [12,49]. The presence of both stx2c and/or stx2d subtypes in a STEC isolate has been associated with human disease, varying from mild to bloody diarrhea and HUS [12,49,50,51,52].…”
Section: Discussionmentioning
confidence: 75%
“…The proportion of individual STEC isolates that carried both stx2c and stx2d concurrently was higher compared to the results of two studies, which previously reported single strains that possess both subtypes [12,49]. The presence of both stx2c and/or stx2d subtypes in a STEC isolate has been associated with human disease, varying from mild to bloody diarrhea and HUS [12,49,50,51,52].…”
Section: Discussionmentioning
confidence: 75%
“…It has previously been reported that the United Kingdom 2015 outbreak was associated with high pathogenicity, and proposed that this was caused by the emergence of a clone that evolved from a STEC O157:H7 stx- negative ancestor after it acquired a bacteriophage encoding Shiga stx2a , which in turn had evolved from a stx2c progenitor ( Byrne et al, 2018 ). The Stx2a subtype has been reported to be most commonly associated with severe disease in humans, while Stx2c and Stx1a much less ( Ostroff et al, 1989 ; Boerlin et al, 1999 ; Orth et al, 2007 ; Kawano et al, 2012 ; Marejková et al, 2013 ; Brandal et al, 2015 ; Legros et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…VT2c, compared to 2a, is statistically associated with HUS although strains tested have been reported to produce less toxin and patients had a lower risk of developing HUS (Kawano et al, 2012;Friedrich et al, 2002). It is also frequently produced in combination with other VT subtypes and associated with eae (Orth et al, 2007).…”
Section: Verotoxin Subtypes and Disease Associationmentioning
confidence: 99%
“…VT2a has been found to be significantly associated with HUS and eae genes (a set of virulence factors involved in colonization of VTEC) and produced significantly higher amounts of toxin compared to other VT2 subtypes (Kawano et al, 2012;Beutin et al, 2004;Friedrich et al, 2002).…”
Section: Verotoxin Subtypes and Disease Associationmentioning
confidence: 99%
See 1 more Smart Citation